2018
DOI: 10.3892/etm.2018.5727
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mono- and combination antibiotic therapy for the treatment of Pseudomonas�aeruginosa bacteraemia: A cumulative meta-analysis of cohort studies

Abstract: It is currently unknown whether antibiotic monotherapy or combination therapy is a more effective treatment for patients with Pseudomonas aeruginosa bacteraemia. The present study consists of a systematic review and meta-analysis of cohort studies in associated studies. The treatment options of monotherapy and combination therapy have been compared, to determine which is more effective against P. aeruginosa bacteraemia. Several electronic bibliographic databases were systematically searched and clinical studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
11
0
2
Order By: Relevance
“…P. aeruginosa predominantly reside in biofilms in the lungs of CF patients, which are also up to 1000 times more resistant to antibiotic treatment than their planktonic counterparts. Antibiotic treatment strategies are still being trialled and optimized for CF patients, and there have been numerous studies comparing mono- and combination-antibiotic therapies [ 32 , 33 ]. Amongst the many alternative therapeutic approaches documented are the guluronate polymer OligoG (derived from alginate), a simple thiol cysteamine, a novel synthetic peptide, nitric oxide and gallium(III) compounds [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…P. aeruginosa predominantly reside in biofilms in the lungs of CF patients, which are also up to 1000 times more resistant to antibiotic treatment than their planktonic counterparts. Antibiotic treatment strategies are still being trialled and optimized for CF patients, and there have been numerous studies comparing mono- and combination-antibiotic therapies [ 32 , 33 ]. Amongst the many alternative therapeutic approaches documented are the guluronate polymer OligoG (derived from alginate), a simple thiol cysteamine, a novel synthetic peptide, nitric oxide and gallium(III) compounds [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that inappropriate antimicrobial therapy and/or delayed initiation of effective antimicrobial therapy is associated with an adverse outcome [4, 10]. However, it is unclear whether combination antimicrobial therapy plays a role in mortality associated with PA bloodstream infections (BSIs) [1114]. Appropriate combination therapy has a favorable effect on survival of patients with febrile neutropenia [15]; however, few studies have focused on antimicrobial therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the 30‐day mortality rate was higher in patients who received monotherapy than those who received combination therapy. One meta‐analysis found that combination therapy could decrease mortality rates in patients with P aeruginosa infection; but another meta‐analysis suggested that combination treatment did not influence patient's outcomes, including mortality 32,33 . Noteworthy, this factor was not recognised as an independent predictor of 30‐day mortality in our final model.…”
Section: Discussionmentioning
confidence: 92%